(untitled) (Journal of Scientific Research, 2011)
A numerical study is conducted to investigate the transport mechanism of mixed convection in an inclined lid-driven triangular enclosure subject to cooling at the inclined right surface and simultaneous heating at the base surface filled with nanofluids. Fluid mechanics and conjugate heat transfer, described in terms of continuity, linear momentum and energy equations, are predicted by using the Galerkin finite element method. Numerical results are obtained for a wide range of parameters such as the Richardson number, tilt angle, and copper-water nanofluids is used with Prandtl number, Pr = 6.2. The streamlines, isotherm plots and the variation of the average Nusselt number at the hot surface as well as average fluid temperature in the enclosure is presented and discussed. It is found that the tilt angle strongly affects the fluid flow and heat transfer in the enclosure at the three convective regimes. Keywords: Copper-water nanofluid; Penalty finite element method; Lid-driven triangular enclosure; Tilt angle; Mixed convection. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7642 J. Sci. Res. 3 (2), 535-548 (2011)